Experimental Study of a Single Droplet Impinging on Dry Surface with and without a Crossflow: Jet Fuel and Biofuel Mixtures - Cunha, Nuno Filipe Costa (2018)
The impact of droplets on different surfaces is a very complex and important phenomenon and it has variety of applications such as fire suppression systems, spray painting, crop spraying and blending preparation in internal combustion engines. Although these phenomena are widely studied, the present work aims to study the influence in mixing a biofuel in a conventional jet fuel and characterize the impact result of the droplets in these mixtures. This study allows the development of numerical models to determine the limit of the different impact phenomena. ln this study, an experimental facility was designed to study the droplet impact behavior on a smooth, dry aluminum surface. Four substances were analyzed: two mixtures (75% JF - 25%HVO and 50% JF - 50% HVO) and two other substances (100% JF and H20). Jet fuel was used to compare the effect of biofuel on the impact result, and H20 was used as the control substance. It was observed that the blends exhibit a different splash / non splash threshold suggesting that the biofuel properties influence the impact result_ To study the effect of a crossflow in this phenomenon , a wind tunnel was also designed and a comparison between normal impact and impact with a crossflow was made. Three crossflow velocities were used and the velocity of the impact was divided into two velocity vectors. Different results were observed comparing crossflow impact with normal impact and the velocity components seem to have some significance in the transition of the impact phenomena. The results were compared with some transition criteria proposed in the literature and the data indicate that none of them presents a good correlation for the data. It was also verified that a study of the surface roughness of the used plate would allow drawing more conclusions.